Successful Endoscopic Transpapillary Management of Intrahepatic Pancreatic Pseudocyst - Kibria, Rizwan; Akram, Salma; Ali, Syed A (JOP. Journal of the Pancreas, 2016)
Context Intrahepatic pancreatic pseudocyst extension is a rare but complex clinical entity requiring multimodality approach for management. There is no consensus regarding the optimal strategy for the treatment of intrahepatic pancreatic pseudocyst and the literature is limited to a few case reports. Most of the published cases were managed by surgical or percutaneous drainage. Case report We hereby report a case of intrahepatic pancreatic pseudocyst extension which failed to resolve by percutaneous drainage. Endoscopic transpapillary drainage was utilized which led to complete resolution of the intrahepatic pancreatic pseudocyst. Conclusion The excellent results obtained in our patient suggest that it should be considered as primary treatment and may obviate the need for more aggressive and potentially morbid procedures. Image: ERCP showing the 7F, 10 cm long pancreatic stent traversing the main duct stricture extending to the tail.